Pitjantjatjara/Yankunytjatjara to English dictionary - Goddard, Cliff; Institute for Aboriginal Development (Alice Springs, N.T.) (Alice Springs, N.T. : Institute for Aboriginal Development, 1992)
Dictionary of Pitjantjatjara and Yankunytjatjara with expanded meanings, gramatical usage and cultural information; includes spelling and pronunciation guide, notes on dialect variation; extensive English to Pitjantjatjara or Yankunytjatjara finder list.
Previous ed. published under title: A Basic Pitjantjatjara/Yankunytjatjara dictionary, 1987.
Includes bibliographical references and index.
Keywords: Pitjantjatjara language -- Dictionaries -- English; Yankunytjatjara language -- Dictionaries -- English; Yankunytjatjara people (C4) (NT SG52-16); Yankunytjatjara language (C4) (NT SG52-16); Language - Vocabulary - Dictionaries and glossaries; Language - Linguistics - Grammar and syntax; Pitjantjatjara people (C6) (NT SG52-11); Pitjantjatjara language (C6) (NT SG52-11); Language - Linguistics - Phonology - Pronunciation; Western Australia (WA); South Australia - Central Australia (SA SG52, SG53); South Central Northern Territory (NT)